TINGKAT PENGETAHUAN MASYARAKAT TENTANG PENGELOLAAN KESEHATAN LINGKUNGAN PERMUKIMAN DI NAGARI SICINCIN KECAMATAN 2X11 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Zahra Maulidya; surtani surtani (JURUSAN GEOGRAFI FIS UNP, 2020)
This study aims to determine the level of public knowledge about the management of environmental health Settlements in Nagari Sicincin District 2x11 Enam Lingkung Padang Pariaman District which includes knowledge about household waste management and knowledge about bathing, washing, and toilet waste management. This type of research is quantitative descriptive. The population of this research is all of the Family Heads in Nagari Sicincin that is 2625 families. The sample in this study was 97 households. Data collection techniques using a questionnaire. Data analysis technique with a percentage. The results showed that: the level of public knowledge about the management of environmental health settlements is still low. This can be seen from the data obtained, only 13.4% of respondents know about household waste management and only 15.46% know about MCK waste management.